Developing Porcine Acellular Dermal Matrix by Using Sodium Dodecyl Sulfate and Biomechanical Property Testing - Medisa Primasari; Iswinarno Doso Saputro; Lynda Hariani; Glorian Paul Bosco Velusamy (Wolters Kluwer - Medknow Publications, 2024)
Introduction: An alternative for supporting wound closure is acellular dermal matrix (ADM), which serves as a scaffold. Humans and porcine possess a similar biochemical makeup. Using sodium dodecyl sulfate (SDS), a decellularization technique was developed and its biomechanical properties were assessed. Methods: This work uses a pig dermis layer for an in vitro experimental investigation with a posttest-only control group. Using SDS 0.5% for 14 days, the decellularization procedure compares the biomechanical properties and cellular components of the ADM with control. The Mann-Whitney U-test for data with a nonnormal distribution or the t-test for continuous variables with a normal distribution was used for the study. Results: Histological analysis revealed that none of the cells were detected in four fields of analysis in the treatment group; however, 48.00 ± 4.86 cells were observed in the control group (P < 0.001); the collagen organization in the control group appeared to be identical. The variables elastic modulus (MPa) (136.78 vs. 129.19; P = 0.556), thickness (mm) (3.27 vs. 3.15; P = 0.397), and width (mm) (8.50 vs. 8.56; P = 0.40) did not differ statistically. The following data showed significant differences between the treatment group and the control group: break strain (%) (108.46 vs. 67.48; P < 0.001) and tensile strength stress (MPa) (19.916 vs. 22.1; P = 0.030). Conclusions: SDS decellularization is an efficient method for creating an ADM. Although the break strain was considerably lower, the treatment group's tensile strength was higher. Elastic modulus changes were not observed.